CONVICT LABOUR AS A FORM OF CORRECTIONAL AND RESOCIALISATION TREATMENT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Convict labor is considered the primary and most effective form of correctional and resocializationtreatment. The importance of convicts work as a form of treatment imposes the need for its further researchin order to create optimal conditions for changing the behavior of convicts involved in the production ofcertain goods. In this paper, the authors will first focus on the stages in the historical development of convictlabour. The second part of the paper presents the most important international documents related to theconvict labour, with reference to different systems of convict work. In the third part, the authors analyze thenormative solutions on convict labour in the Republic of Serbia, with reference to the situation in Serbianpenitentiaries. Finally, the authors suggest how the application of this form of treatment may be improvedin penitentiary institutions.
Keywords: convict labour, treatment, resocialization.